Remediation of persistent organic pollutants through statistical treatment using the CoFe2O4@Fe3O4-based magnetic nanocomposite - Costa, José Arnaldo S. [UNESP]; Oliveira, Rhayza Victoria M.; Menezes, Thalles Henrique S.; Costa, Vinicius C.; Romão, Luciane P.C. [UNESP]; Paranhos, Caio Marcio (Elsevier, 2024)
In the present study, the CoFe2O4@Fe3O4-based magnetic nanocomposite was synthesized and applied as an adsorbent material in the polycyclic aromatic hydrocarbons (PAHs) remediation, which include phenanthrene (Phe), benzo[b]fluoranthene (B[b]F), benzo[k]fluoranthene (B[k]F), and benzo[a]pyrene (B[a]P). The experimental conditions were investigated using a factorial experimental design (24) with the aim of carrying out a systematic evaluation of the solution pH, equilibrium time, concentration of pollutants, and magnetic nanocomposite mass. The characterization of the CoFe2O4@Fe3O4 adsorbent by the FTIR and XRD analyses showed success in the formation of magnetic nanoparticles. In addition, the SEM–EDS analysis exhibited images of nanometric spheres, uniform morphology, and the presence of Fe, Co and O as main components, as well as a type IV isotherms with H1 hysteresis as a typical formation of a mesoporous nanocomposite with high surface area (244.28 m2 g−1) and large pore volume (0.19 cm3 g−1). The statistical treatment revealed that the pH and the adsorption time are variables that little or nothing influenced the adsorptive properties of the CoFe2O4@Fe3O4 to remove the PAHs mixture, contrary to the PAHs concentration and the CoFe2O4@Fe3O4 mass, which are important variables. Finally, the best experimental conditions were obtained for the adsorption tests between 13 (pH 3, time = 5 min, concentration = 1000 µg L−1, and mass = 50 mg) and 16 (pH 10, time = 200 min, concentration = 1000 µg L−1, and mass = 50 mg), whose overall desirability (OD) values were 1.00 and removal efficiency varied between 92.40 and 96.60 %; 95.00–97.00 %; 90.80–96.30 %; and 93.50–96.80 %, respectively, for Phe, B[b]F, B[k]F, and B[a]P.
Keywords: Adsorption; CoFe2O4@Fe3O4; Ferrites; PAHs; Persistent organic pollutants